1982
DOI: 10.1037/0022-3514.43.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Individual construct accessibility and subjective impressions and recall.

Abstract: Two studies examined the role of individual differences in construct accessibility in subjective impressions and recall of others. In the first session of each study, subjects' accessible traits were elicited by asking them to list the characteristics of different people, with accessibility defined as frequency of output (Study 1) or as primacy of output (Study 2). In the second session, held 1 or 2 weeks later and supposedly investigating a different issue for a different researcher, subjects read an essay de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
406
0
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 595 publications
(422 citation statements)
references
References 39 publications
12
406
0
4
Order By: Relevance
“…In light of these and other findings, Higgins, King, and Mavin (1982) have suggested that a similarity between judgments of the self and others may be attributable, at least in part, to differences in chronic accessibility. For example, highly sociable subjects who are asked to form sociability judgments of an ambiguous behavior may be more likely to encode this statement as sociable relative to subjects whose own position is less extreme (and therefore, for whom that trait concept may be less accessible).…”
Section: Encoding Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these and other findings, Higgins, King, and Mavin (1982) have suggested that a similarity between judgments of the self and others may be attributable, at least in part, to differences in chronic accessibility. For example, highly sociable subjects who are asked to form sociability judgments of an ambiguous behavior may be more likely to encode this statement as sociable relative to subjects whose own position is less extreme (and therefore, for whom that trait concept may be less accessible).…”
Section: Encoding Effectsmentioning
confidence: 99%
“…For example, highly sociable subjects who are asked to form sociability judgments of an ambiguous behavior may be more likely to encode this statement as sociable relative to subjects whose own position is less extreme (and therefore, for whom that trait concept may be less accessible). As Higgins et al (1982) were careful to note, however, this process does not necessarily involve direct access of self-relevant knowledge. That is, similarity in self-other judgments may simply reflect a tendency for some individuals to use certain constructs in processing information about people in general, including the self.…”
Section: Encoding Effectsmentioning
confidence: 99%
“…Activated, salient possible selves organize and energize individuals" behavior aimed at bringing them about (Leonardi, Syngollitou, & Kiosseoglou, 1998). Like other mental constructs, identities can become chronically accessible if they are activated and used frequently (Bargh, 1982;Higgins, King, & Mavin, 1982;Srull & Wyer, 1986). The salience of Future Work Selves thus develops over time as individuals think about their hopes and aspirations for their future, observe role models (Ibarra, 1999), and consider who they might become.…”
Section: Future Work Selves and The Importance Of Saliencementioning
confidence: 99%
“…Following the research logic of Higgins, King, and Mavin (1982), we assumed that such order reflects the strength of association between the goal and the individuals mentioned, or the accessibility of their names once the goal was activated. In summary then, we hypothesized that participants will develop a preventiontype affect toward people strongly associated with helping them to attain ought goals, whereas they will develop a promotion-type affect toward persons strongly associated with helping them attain ideal goals.…”
Section: Study 5: the Transfer Of Affective Qualities To Social Meansmentioning
confidence: 99%